Schistosomiasis and Infertility: What Do We Know? - Ribeiro, Ana Rita (2019)
There is increasing attention on the complex interactions occurring between schistosome parasites and their hosts. However, little is known about the occurrence, epidemiology, and mechanisms of schistosomiasis-associated infertility. In this article, we argue that an in-depth understanding of the interplay between parasites and the host endocrine system may significantly enhance current knowledge of infertility in infected individuals. We discuss the basic hormonal mechanisms that may lead to the discovery of entirely novel anthelmintic interventions against schistosomiasis.